Kingmakers and leaders in coalition formation - Marc Kilgour; Steven J. Brams (Fondazione Eni Enrico Mattei (FEEM), 2009)
Assume that players strictly rank each other as coalition partners. We propose a procedure whereby they fall back on their preferences, yielding internally compatible, or coherent, majority coalition(s), which we call fallback coalitions. If there is more than one fallback coalition, the players common to them, or kingmakers, determine which fallback coalition will form. The players(s) who are the first to be acceptable to all other members of a fallback coalition are the leader(s) of that coalition. The effects of different preference assumptions-particularly, different kinds of single-peakedness - and of player weights on the number of coherent coalitions, their connectedness, and which players become kingmakers and leaders are investigated. The fallback procedure may be used (i) empirically to identify kingmakers and leaders or (ii) normatively to select them.
Keywords: C71; C78; D72; 330; Coalition; Fallback Process; Kingmaker Leader; Cardinally Single-peaked; Ordinally Single-peaked